Combination of blood flow asymmetry in the cerebral and cerebellar hemispheres on brain perfusion SPECT predicts 5-year outcome in patients with symptomatic unilateral major cerebral artery occlusion. (March 2014) - Nomura, Jun-ichi; Ogasawara, Kuniaki; Saito, Hideo; Terasaki, Kazunori; Matsumoto, Yoshiyasu; Takahashi, Yoshihiro; Ogasawara, Yasushi; Saura, Hiroaki; Yoshida, Koji; Sato, Yuiko; Kubo, Yoshitaka; Ogawa, Akira
<x content-type="archive" xml:space="preserve">Abstract</x> Background and objective: Misery perfusion increases the risk of stroke recurrence in patients with symptomatic major cerebral artery occlusion. The ratio of brain perfusion contralateral-to-affected asymmetry in the cerebellar hemisphere to brain perfusion affected-to-contralateral asymmetry in the cerebral hemisphere (CblPR/CbrPR) indicates affected-to-contralateral asymmetry of oxygen extraction fraction (OEF) in the cerebral hemisphere. The purpose of the present study was to determine whether the CblPR/CbrPR on brain perfusion single-photon emission computed tomography (SPECT) predicts 5-year outcomes in patients with symptomatic unilateral occlusion of the middle cerebral artery (MCA) or internal carotid artery (ICA). Methods: Brain perfusion was assessed using N-isopropyl-p-[123I]-iodoamphetamine (123I-IMP) SPECT in 70 patients. A region of interest (ROI) was manually placed in the bilateral MCA territories and in the bilateral cerebellar hemispheres, and the CblPR/CbrPR was calculated. All patients were prospectively followed for 5 years. The primary end points were stroke recurrence or death. Results: A total of 17 patients exhibited the primary end points, 11 of whom experienced subsequent ipsilateral strokes. Multivariate analysis revealed that only high CblPR/CbrPR was significantly associated with the development of the primary end point or subsequent ipsilateral strokes (95% confidential limits [CIs], 1·130–3·145; P = 0·0114 or 95% CIs, 2·558–5·140; P = 0·0045, respectively). The CblPR/CbrPR provided 65% (11/17) or 91% (10/11) sensitivity and 88% (47/53) or 88% (52/59) specificity in predicting the primary end point or subsequent ipsilateral strokes, respectively. Conclusions: The CblPR/CbrPR on brain perfusion SPECT predicts 5-year outcomes in patients with symptomatic unilateral occlusion of the MCA or ICA.